EVALUATION OF DIET AND FUNCTIONAL TRAITS OF CYPRINUS CARPIO IN THE THIRD RIVER/ CENTRAL IRAQ - Kadhim J. L. Al- Zaidy; Giuliana Parisi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted in the Third River for the extended period from January 2022 to December 2022. A total of 327 Cyprinus carpio fish were collected. The measurements were carried out to show the monthly changes in food selection, some of the functional traits that influence feeding were also measured. The results showed that the highest rate of stomach values containing food was found in the months of May and July, while the highest level of feeding intensity was recorded in November. The results of the study suggested that the standard length for tested fish was 342.5±88.5.mm. Head length, and head depth were 77.91± 18.12 mm and 64.91± 15.03 mm consecutively. The study concluded that the functional traits exhibited by common carp improved their ability to adapt to their environment and that their status is not sensitive in the study area.